Low carbohydrate diets and sport - Jan Vyjidák (Matej Bel University, 2021)
Recently, athletes have become more interested in low carbohydrates (CHO) diets (LCD, LCHF), whether for performance or health reasons. This short review paper summarises the current dietary recommendations for sports, introduces LCDs, highlights some of the important historical developments, introduces the concept of "fuel for the work required" and presents selected reports, case studies, and studies. It provides a brief overview of some of the key risks and disadvantages of LCDs in athletes without and with diabetes. DOI: https://doi.org/10.24040/sjss.2021.7.1.77-88